Characterisation of Colletotrichum siamense TD1 causing anthracnose leaf spots of Camellia tamdaoensis Ninh et Hakoda at the Tam Dao National Park - Hong Viet La; Duc Hoang Le; Thao Thanh Thi Duong; Bang Phi Cao; Ha Duc Chu (Vietnam Journal of Science, Technology and Engineering, 2023)
Camellia L. is a precious medicinal plant with 16 different species and high economic value. In Tam Dao National Park, Vinh Phuc, Camellia L. is rich in ingredients. Anthracnose is a severe disease caused by fungi on the leaves of Camellia L., however, research of the fungus causing anthracnose on leaves of Camellia L. in Vietnam remains limited. In this study, anthracnose-infected leaves of Camellia tamdaoensis Ninh et Hakoda in Tam Dao National Park were collected, and the causative agent was isolated. Eleven fungal strains that cause anthracnose were obtained through gene sequence identification of the internal transcribed spacer (ITS) region. One fungal strain was selected to isolate DNA and determine the gene sequence of the ITS region. Based on this ITS sequence, the causative agent on leaves of C. tamdaoensis Ninh et Hakoda was Colletotrichum siamense TD1. The ITS sequence was determined to be 522 bp in length, 52.30% of guanine-cytosine (GC) content, and was registered on GenBank with accession number OK560718. Pathogenicity tests were conducted to fulfil Koch’s postulates. This is the first report of anthracnose leaf spots of C. tamdaoensis Ninh et Hakoda caused by C. siamense TD1 in Vietnam. The results of anthracnose fungi provide helpful information for disease management and are necessary for future studies on selecting disease-resistant varieties of Camellia L.